ANALISIS YURIDIS TOP UP GAME OLEH ANAK BERDASARKAN HUKUM PERLINDUNGAN KONSUMEN DAN PERLINDUNGAN ANAK - I Kadek Budiatmika; Si Ngurah Ardhya; Ratna Artha Windari; Komang Febrinayanti Dantes; I Wayan Empu Guana Pura (Jurnal Ilmu Hukum Sui Generis, 2026)
The development of digital gaming industry has led to a surge in game top-up transactions that involve not only adult consumers, but also minors. The characteristics of top-up transactions, which are instant, repetitive, and directly integrated with the game mechanism, have the potential to encourage impulsive consumption behavior in children who are psychologically and legally immature in making economic decisions. This article aims to analyze game top-up transactions made by minors from the perspective of consumer protection law and child protection law. This study uses a normative legal research method with a legislative and conceptual approach, through analysis of the Civil Code, the Consumer Protection Law, and the Child Protection Law. The results of the study indicate that game top-up transactions by children raise issues of contract validity due to the lack of the element of legal capacity, and place children as digital consumers who are vulnerable to harmful economic practices. Furthermore, the absence of specific regulations regarding digital transactions involving children means that the responsibilities of game operators and digital platforms are not clearly defined. Therefore, it is necessary to strengthen regulations and clarify the responsibilities of operators to ensure effective legal protection for children in game top-up transactions.